2010
DOI: 10.1080/17467586.2010.531029
|View full text |Cite
|
Sign up to set email alerts
|

Grievance, social dominance orientation, and authoritarianism in the choice and justification of terror versus protest

Abstract: The present research examines the extent to which grievance and socialpersonality factors including Social Dominance Orientation (SDO) and Right Wing Authoritarianism (RWA) influence support for and justification of both peaceful and violent forms of political action. Using an experimental design that manipulated level of grievance, we asked a sample of 2932 US adult participants to read a vignette, and then to indicate their likelihood of engaging in any form of political action as a result of the experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…A recent meta-analysis assessed research related to antisemitism and antigypsyism between 2005 and 2017 in Hungary revealed that right-wing authoritarianism is a more important predictor of anti-minority attitudes than SDO (Kende et al, 2018). We did not include relative deprivation, political alienation, and low political power, as they are all antecedents of radical protest (see e.g., Daskin, 2016;Lemieux & Asal, 2010;Muller & Jukam, 1983;Staub, 1999Staub, , 2000. We only measured the propensity for radical protest, as it is an expression of strong political discontent and dissatisfaction (Muller & Jukam, 1983), but it would be useful in future studies to also investigate its antecedents as separate predictors of intergroup violence.…”
Section: Limitations Conclusion and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis assessed research related to antisemitism and antigypsyism between 2005 and 2017 in Hungary revealed that right-wing authoritarianism is a more important predictor of anti-minority attitudes than SDO (Kende et al, 2018). We did not include relative deprivation, political alienation, and low political power, as they are all antecedents of radical protest (see e.g., Daskin, 2016;Lemieux & Asal, 2010;Muller & Jukam, 1983;Staub, 1999Staub, , 2000. We only measured the propensity for radical protest, as it is an expression of strong political discontent and dissatisfaction (Muller & Jukam, 1983), but it would be useful in future studies to also investigate its antecedents as separate predictors of intergroup violence.…”
Section: Limitations Conclusion and Future Directionsmentioning
confidence: 99%
“…Violencefor example in the context of protestscan be an expression of strong political discontent (Muller & Jukam, 1983), grievance (Lemieux & Asal, 2010), or the outcome of intergroup situations that are perceived stable and illegitimate (Livingstone, Spears, Manstead, & Bruder, 2009;Scheepers, Spears, Doosje, & Manstead, 2006). Discontent can be explained by group-basedso-called "fraternal"relative deprivation (Runciman, 1966), when people feel that their group is at a disadvantaged compared to other groups or their situation improves less than that of other groups, resulting in feelings of injustice and resentment.…”
mentioning
confidence: 99%
“…There are a few notable exceptions. Lemieux and Asal (2010), for instance, assessed the influence of RWA on support for peaceful and violent forms of political action in response to reading a vignette that manipulated level of grievance. They found that respondents who were high in RWA were generally less inclined to support any form of political action.…”
Section: Authoritarianism and Camentioning
confidence: 99%
“…Those who actively liked the material also tended to have higher SDO than those who did not, which supports other research suggesting that high SDO individuals are more likely to interact with extremist propaganda than those who are not. 87 Similarly, likes were also more likely to be associated with OGH. These results suggest that like and dislike interactions are important for researchers in evaluating engagement in extremist online material in several ways.…”
Section: Part 2 Discussionmentioning
confidence: 97%